First record of the subfamily Anoplophilinae (Orthoptera: Rhaphidophoridae) from Russia with description of a new species of the genus Alpinanoplophilus Ishikawa, 1993 - Storozhenko, Sergey Yu. (Zootaxa, 2015)
The subfamily Anoplophilinae (Rhaphidophopridae) is recorded from Russia for the first time. Alpinanoplophilus kurilensis Storozhenko, sp. nov. is described from Kunashir Island. The holotype of the new species is deposited in the Zoological Institute of Russian Academy of Science (St. Petersburg, Russia). A revised key to the species of the genus Alpinanoplophilus Ishikawa, 1993 is provided.